Autecology of Melastoma malabathricum, an invasive species in the Way Kambas National Park, Indonesia - JANI MASTER; IBNUL QAYIM; DEDE SETIADI; NYOTO SANTOSO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Master J, Qayim I, Setiadi D, Santoso N. 2020. Autecology of Melastoma malabathricum, an invasive species in the Way Kambas National Park, Indonesia. Biodiversitas 21: 2303-2310. Melastoma malabathricum has become one of the invasive plants in the Way Kambas National Park (WKNP), Lampung, Indonesia. This plant is feared to be a problem in efforts to conserve biodiversity in the WKNP area. Therefore, this study aimed to analyze the factors causing the invasion of these plants. The vegetation analysis plot was placed on three types of habitats in the study location, namely, forests, swamps, and invaded swamps, then measurements and records of vegetation data and abiotic factors were recorded in each plot. The results reveal that M. malabathricum dominates swamp habitat and negatively associated with trees, which can provide canopy. Abiotic factors, such as canopy cover, water level, and soil fertility, become supporting factors for the invasion. In addition, climate change, which is causing drought also contributes to the invasion of M. malabathricum at the WKNP.